Cultivating Compassion: Assessing the Impact of Virtual Group Guidance and Modeling Techniques on Heightening Students' Charity Enthusiasm - Zhila Jannati; Abdullah Idi; Dian Erlina (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to analyze the effectiveness of virtual group guidance using modeling techniques to increase students' interest in giving alms in terms of input, output and implementation process. The research method used is mixed methods, namely embedded design. This research involved class X students using purposive sampling, namely ten students for the experimental group and the control group. Researchers used research instruments on the psychological scale of interest in giving alms, interviews, observation and documentation. The research results found that 1) virtual group guidance using modeling techniques was proven to be effective in increasing students' interest in giving alms in terms of input and output. This is based on the pre-test score obtained in the experimental group, namely 165 (61.34%) in the poor category. Meanwhile, the average post-test score was 213.9 (79.81%) in the medium category. The sig (2-tailed) value obtained is 0.002 where 0.002 0.05 from the results of the Paired Sampled T-Test. So, it is proven that there is a significant difference when compared before and after the treatment is applied. The Independent Sampled T-Test also shows that the sig (2-tailed) value is 0.008 where 0.008 0.05 so it can be said that the experimental group is different from the control group regarding their average interest in giving alms; and 2) virtual group guidance with modeling techniques has proven to be effective in increasing students' interest in giving alms in terms of the implementation process which can be seen from the aspects of communication, resources, disposition and bureaucratic structure, all of which are in the high category.